Phosphorylation of TGIF2 represents a therapeutic target that drives EMT and metastasis of lung adenocarcinoma - Du, Renle; Wang, Chen; Liu, Jingjing; Wang, Keyan; Dai, Liping; Shen, Wenzhi (BMC cancer, 2023)
TGF-β-induced factor homeobox 2 (TGIF2) is a transcription regulator that is phosphorylated by EGFR/ERK signaling. However, the functions of phosphorylated (p)-TGIF2 in cancer are largely unknown. Here, we investigated the roles of p-TGIF2 in promoting epithelial-mesenchymal transition (EMT) and metastasis in lung adenocarcinoma (LUAD). In vitro and in vivo experiments were conducted to investigate the role of TGIF2 in LUAD EMT and metastasis. Dual-luciferase reporter and ChIP assays were employed to observe the direct transcriptional regulation of E-cadherin by TGIF2 and HDAC1. Co-immunoprecipitation was performed to identify the interaction between TGIF2 and HDAC1. Downregulating the expression of TGIF2 inhibited LUAD cell migration, EMT and metastasis in vitro and in vivo. Phosphorylation of TGIF2 by EGFR/ERK signaling was required for TGIF2-promoted LUAD EMT and metastasis since phosphorylation-deficient TGIF2 mutant lost these functions. Phosphorylation of TGIF2 was necessary to recruit HDAC1 to the E-cadherin promoter sequence and subsequently suppress E-cadherin transcription. Meanwhile, inhibition of HDAC1 repressed the TGIF2 phosphorylation-induced migration and EMT of LUAD cells. In xenograft mouse models, both inhibition of ERK and HDAC1 could significantly inhibited TGIF2-enhanced metastasis. Furthermore, TGIF2-positive staining was significantly correlated with E-cadherin-negative staining in human lung cancer specimens. Our study reveals the novel function of p-TGIF2 in promoting EMT and metastasis in LUAD; p-TGIF2 could be a potential therapeutic target to inhibit LUAD metastasis.